Cardiac risks and management of complications in pregnant women with congenital heart disease. (March 2012) - Hatton, Rachael; Colman, Jack M; Sermer, Mathew; Grewal, Jasmine; Silversides, Candice K
There are a growing number of women with congenital heart disease reaching adulthood and contemplating and/or undergoing pregnancy. However, pregnancy imposes hemodynamic stress on the heart and this can result in maternal, fetal and neonatal complications. Most women with congenital heart disease do well during pregnancy, but some women with high-risk cardiac lesions will not tolerate the hemodynamic changes of pregnancy. Physicians must be aware of the potential risks for the mother both during and after pregnancy, the risks to the fetus and neonate, and the risks and benefits of medications and procedures used during pregnancy. For women with complex cardiac conditions, management during pregnancy benefits from multidisciplinary care involving cardiologists with expertise in pregnancy, obstetricians with expertise in maternal fetal medicine, neonatologists and obstetric anesthetists, among others. This review will focus on the cardiac risks faced by women with congenital heart disease; particularly those at high risk, and on management strategies to mitigate risk and address cardiac complications.